Eosinophilic Appendicitis – A Case Series Of 5 Cases And Review Of Literature - M. Shinde, Chaitanya; Kanetkar, Sujata R. (Journal of Neonatal Surgery, 2025)
Eosinophilic appendicitis, a rare condition mimicking acute appendicitis, involves eosinophil infiltration of the appendix. This study analyzed 268 appendectomy specimens, identifying five cases of eosinophilic appendicitis (2.6% incidence). We suggest appendectomy is beneficial in these cases to prevent future acute appendicitis. The pathogenesis may involve a Type 1 hypersensitivity reaction